The Impact of Psychological and Physiological Conditions of Motherhood on Postnatal Depression - Vera A. Yakupova (Rossijskij psihologičeskij žurnal., 2018)
Introduction. The paper (a) discusses psychological and physiological conditions of motherhood among women at risk of postnatal depression, (b) overviews studies on depression risk factors, and (c) presents the results of the original study. This research concentrates on mothers’ views of their own experience of motherhood and also their personality traits. The present study develops and validates diagnostic tools for identifying women at risk of depression. Methods. The study employed the Edinburgh Postnatal Depression Scale (EPDS), Beck Depression Inventory, and the author’s questionnaire on motherhood conditions. Results. The study involved mothers (n = 151) of babies under one year old. The conducted study helped to reveal a group of women at risk of postnatal depression. Sleep-deprived mothers (sleeping less than 7 hours per day) not feeling a constant support from their husbands fell into this risk group. The risk group mothers underwent a difficult labor; they had unrealistic expectations of motherhood. Discussion. The following factors determine the risks of postnatal depression: (a) a woman’s expectations of motherhood, (b) her views of parenthood realities, (c) the context of marital relations, and (d) psychological conditions of parenthood. The research findings can be readily used in practice.